2016
DOI: 10.1039/c6sm00619a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elongational flow on immiscible polymer blend/nanoparticle composites: a molecular dynamics study

Abstract: Using coarse-grained nonequilibrium molecular dynamics, the dynamics of a blend of the equal ratio of immiscible polymers mixed with nanoparticles (NP) are simulated. The simulations are conducted under planar elongational flow, which affects the dispersion of the NPs and the self-assembly morphology. The goal of this study is to investigate the effect of planar elongational flow on the nanocomposite blend system as well as to thoroughly compare the blend to an analogous symmetric block copolymer (BCP) system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Under the interaction region from ε np = 1.0ε pp to 4.0ε pp , the particles display several layers to form sandwich-like structure, depending upon both the shear flow and particle−polymer interaction. Such ordered structure has also been reported in previous simulation 17 and experiment. 54 With the increase of the interaction strength, the number of layers slightly decreases, but the distance between the adjacent layers increases.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Under the interaction region from ε np = 1.0ε pp to 4.0ε pp , the particles display several layers to form sandwich-like structure, depending upon both the shear flow and particle−polymer interaction. Such ordered structure has also been reported in previous simulation 17 and experiment. 54 With the increase of the interaction strength, the number of layers slightly decreases, but the distance between the adjacent layers increases.…”
Section: Resultssupporting
confidence: 88%
“…Molecular dynamic simulations and statistical mechanic theories provide reliable methods to yield microscopic insights into the diffusion of particles in polymer systems under various shear conditions. In some simulations, the influences of shear flow on particle dispersion states were clearly displayed via particle coordinates. It was shown that a suitable shear strength can result in particle aggregation, sandwich-like structure formation, and homogeneous particle dispersion in polymer matrix with an increase of particle–polymer interaction . A shear field also played an important role in particle distribution in the cases of symmetric block copolymers but had little effect on the immiscible polymer blend/particle composites .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For many practical applications, the addition of nanoparticles has been considered as an effective route to material improvement and an important method for creating highly ordered structures. [12][13][14][15][16] In particular, the addition of anisotropic nanoparticles (such as nanorods) to polymeric materials can be beneficial and increase their photoelectric characteristics, optical properties and mechanical properties. [17][18][19][20][21][22][23] The nanorods of noble metals (such as gold) and semiconductors (such as CdSe) possess interesting photoelectrical properties and can significantly improve the efficiency of polymer photovoltaic devices by enhancing their carrier mobilities.…”
Section: Introductionmentioning
confidence: 99%